El concepto de igualdad de oportunidades. Análisis de sus perspectivas (2021)
The article analyzes theories that have studied the concept of equal opportunity or that have examined inequality in school. The ideas proposed by the French sociology of education represented by Pierre Bourdieu, Jean Claude Passeron, Raymond Boudon, and François Dubet are reviewed. Some ideas around access to higher education and how these proposals determine its analysis are studied. Bourdieu and Passeron study the democratization of education and how social origin is related to educational level. They also discuss why school, instead of dissipating inequalities, increases them. Boudon, on the other hand, describes from a more liberal perspective the relationship between education and the role of the individual and his or her decisions; this theory will demonstrate with large statistics the methodological individualism that investigates how family and personal decisions determine social mobility. Finally, Dubet belongs to another generation that explicitly analyzes equality of opportunities as opposed to equality of positions; in addition, he examines how societies manufacture via neoliberal policies more exclusion through academic degrees and their impact on societies. These theories help to construct a conceptualization of equal opportunities and to determine how they affect public policies in higher education and what impact they have on the reality of young people who seek educational opportunities.